(untitled) (Taqdir, 2025)
This study aims to develop a digital thematic dictionary to support Arabic vocabulary instruction at Madrasah Tsanawiyyah Quranic Scientia. The method used is Research and Development (R&D), employing the ADDIE model by Dick & Carey, which includes five stages: analysis, design, development, implementation, and evaluation. Data were collected through questionnaires, observations, interviews, tests, and documentation. The needs analysis showed that 90.91% of teachers and 85.83% of students indicated a strong need for a digital dictionary. Media validation reached 91.11%, and content validation reached 97.5%, placing the product in the “excellent” category. The final product is a dictionary in APK (Android Package) format. The Paired Samples T-Test produced a t-value of 2.991, which is greater than the t-table value of 2.145, proving that this digital thematic dictionary is effective in enhancing the vocabulary mastery of seventh-grade students at Quranic Scientia, UIN Imam Bonjol Padang.